2019
DOI: 10.3390/ijerph16010159
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Knowledge among Adults with Cardiometabolic Risk Factors: A Cross-Sectional Study

Abstract: Metabolic syndrome (MetS) is a cluster of cardiometabolic risk factors. Many people may be unaware of their risk for MetS. A cross-sectional, descriptive study was conducted among hospitalized patients with at least one cardiometabolic risk factor in Mainland China. This study assessed the MetS knowledgelevel(through MetS Knowledge Scale, MSKS) and examined the potential predictors by regression analysis. A total of 204 patients aged 58.5 ± 10.1 years (55% males) participated in this study. The majority of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
8
10
0
3
Order By: Relevance
“…Outro estudo transversal, (3) também identificou baixo nível de conhecimento da SM em adultos (n= 113; 58,5±10,1 anos), com fatores de risco cardio-metabólicos. E demonstrou resultados interessantes, verificou-se que as variáveis de maior tempo de escolaridade (entre 9 a 12 anos ou > 12 anos), história pregressa de dislipidemia e nível normal de HDL-c são características preditoras do conhecimento sobre SM, muito provavelmente, devido a relação de causa-efeito entre o aumento do conhecimento da SM e melhor gerenciamento do cuidado de si mesmo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Outro estudo transversal, (3) também identificou baixo nível de conhecimento da SM em adultos (n= 113; 58,5±10,1 anos), com fatores de risco cardio-metabólicos. E demonstrou resultados interessantes, verificou-se que as variáveis de maior tempo de escolaridade (entre 9 a 12 anos ou > 12 anos), história pregressa de dislipidemia e nível normal de HDL-c são características preditoras do conhecimento sobre SM, muito provavelmente, devido a relação de causa-efeito entre o aumento do conhecimento da SM e melhor gerenciamento do cuidado de si mesmo.…”
Section: Discussionunclassified
“…E demonstrou resultados interessantes, verificou-se que as variáveis de maior tempo de escolaridade (entre 9 a 12 anos ou > 12 anos), história pregressa de dislipidemia e nível normal de HDL-c são características preditoras do conhecimento sobre SM, muito provavelmente, devido a relação de causa-efeito entre o aumento do conhecimento da SM e melhor gerenciamento do cuidado de si mesmo. (3) Portanto, a constatação do desconhecimento da SM na linha de base dos dois grupos concordam com achados de estudos transversais anteriores. (2,21) Satisfatoriamente, conseguiu-se melhorar o nível de conhecimento sobre SM e dos seus fatores de risco após seis meses de intervenção de um programa educativo de promoção da saúde.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Prevention and early detection of metabolic syndrome is an important effort in reducing the incidence of this disease. Increasing awareness and knowledge of metabolic syndrome through specific health education can improve the quality of public health, considering that public knowledge of this disease is still low 11 . In this program, there was a 76.9% increase in people's knowledge regarding metabolic syndrome, which was assessed from the results of the pre-test and post-test.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated adequate knowledge on management and prevention of MetS would enable people's adaptation to healthy behaviors [11,12]. The lifestyle modification is the most efficient policy or strategy to manage metabolic syndrome.…”
mentioning
confidence: 99%